2010
DOI: 10.1182/blood-2009-04-216069
|View full text |Cite
|
Sign up to set email alerts
|

Novel function for blood platelets and podoplanin in developmental separation of blood and lymphatic circulation

Abstract: During embryonic development, lymph sacs form from the cardinal vein, and sprout centrifugally to form mature lymphatic networks. Separation of the lymphatic from the blood circulation by a hitherto unknown mechanism is essential for the homeostatic function of the lymphatic system. O-glycans on the lymphatic endothelium have recently been suggested to be required for establishment and maintenance of distinct blood and lymphatic systems, primarily by mediating proper function of podoplanin. Here, we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
256
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(268 citation statements)
references
References 52 publications
8
256
1
1
Order By: Relevance
“…However, many other different transcription factors regulate lymphatic development. Interestingly, it has been shown that during embryogenesis, lymphatic system separation from blood vessels requires platelet activity 7. Indeed, platelets regulate the blood/lymphatic vessel separation by inhibiting the proliferation, migration, and tube formation of LECs, upon the interaction of C‐type lectin‐like receptor 2 (CLEC‐2) with podoplanin 8.…”
Section: Introductionmentioning
confidence: 99%
“…However, many other different transcription factors regulate lymphatic development. Interestingly, it has been shown that during embryogenesis, lymphatic system separation from blood vessels requires platelet activity 7. Indeed, platelets regulate the blood/lymphatic vessel separation by inhibiting the proliferation, migration, and tube formation of LECs, upon the interaction of C‐type lectin‐like receptor 2 (CLEC‐2) with podoplanin 8.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, podoplanin-deficient mice fail to develop a functional lymphatic system with a severe lymphedema in the extremities . A series of recent findings has shown that podoplanin activates a novel platelet receptor, C-type lectinlike receptor (CLEC)-2 of platelet, and has an essential role in blood -lymphatic separation during lymphatic development (see more information below) (Fu et al 2008;Kato et al 2008;Bertozzi et al 2010a,b;Suzuki-Inoue et al 2007Uhrin et al 2010;SuzukiInoue 2011). Moreover, some lymphatic vessels were found to express a high level of podoplanin (LEC podo-high ) and the others a low level of podoplanin (LEC podo-low ), and these two subpopulations differentially recruit CCR10-positive T lymphocytes during the inflammation response (Kriehuber et al 2001;Wick et al 2008).…”
Section: Initial Steps For Lymphatic Specification and Differentiationmentioning
confidence: 99%
“…These pioneering findings were followed by a series of molecular and genetic studies confirming the role of podoplanin/CLEC-2 interaction in lymphatic development. Notably, endothelial cell O-glycan deficiency caused blood/lymphatic misconnection in mouse (Fu et al 2008), and podoplanin or CLEC-2 knockout mice showed the blood -lymphatic mixing phenotype of mice lacking SYK, SLP-76, or PLCg-2 (Bertozzi et al 2010a,b;Suzuki-Inoue et al 2010;Uhrin et al 2010). Together, these studies show that the platelets mediate blood and lymphatic separation by activation of the CLEC-2 receptor following interaction with the podoplanin ligand found on the surface of LECs.…”
Section: Lymphatics the Other Circulatory Systemmentioning
confidence: 99%
“…Binding of the snake venom rhodocytin or Pdpn to CLEC-2 on platelets triggers intracellular signaling via Syk-SLP76 that leads to platelet activation (15). The molecular interaction between Pdpn and CLEC-2 has been shown to be important in the development of the lymphatic system, as it is involved in the physical separation of the lymph sacs from the blood-filled cardinal vein (16,17). Also, CLEC-2-positive dendritic cells interact with Pdpn-positive LEC and follicular reticular cells for their migration from the periphery to and through the lymph node where they present antigens to T-cells (18).…”
mentioning
confidence: 99%